RNA-Sequencing Reveals Unique Transcriptional Signatures of Running and Running-Independent Environmental Enrichment in the Adult Mouse Dentate Gyrus - Grégoire, Catherine-Alexandra; Tobin, Stephanie; Goldenstein, Brianna L.; Samarut, Éric; Leclerc, Andréanne; Aumont, Anne; Drapeau, Pierre; Fulton, Stephanie; Fernandes, Karl J. L. (Frontiers in Molecular Neuroscience, 2018)
Environmental enrichment (EE) is a powerful stimulus of brain plasticity and is among the most accessible treatment options for brain disease. In rodents, EE is modeled using multi-factorial environments that include running, social interactions, and/or complex surroundings. Here, we show that running and running-independent EE differentially affect the hippocampal dentate gyrus (DG), a brain region critical for learning and memory. Outbred male CD1 mice housed individually with a voluntary running disc showed improved spatial memory in the radial arm maze compared to individually- or socially-housed mice with a locked disc. We therefore used RNA sequencing to perform an unbiased interrogation of DG gene expression in mice exposed to either a voluntary running disc (RUN), a locked disc (LD), or a locked disc plus social enrichment and tunnels (i.e., a running-independent complex environment, CE). RNA sequencing revealed that RUN and CE mice showed distinct, non-overlapping patterns of transcriptomic changes versus the LD control. Bio-informatics uncovered that the RUN and CE environments modulate separate transcriptional networks, biological processes, cellular compartments and molecular pathways, with RUN preferentially regulating synaptic and growth-related pathways and CE altering extracellular matrix-related functions. Within the RUN group, high-distance runners also showed selective stress pathway alterations that correlated with a drastic decline in overall transcriptional changes, suggesting that excess running causes a stress-induced suppression of running’s genetic effects. Our findings reveal stimulus-dependent transcriptional signatures of EE on the DG, and provide a resource for generating unbiased, data-driven hypotheses for novel mediators of EE-induced cognitive changes.